How prostacyclin therapy improves right ventricular function in pulmonary arterial hypertension. Issue 2 (24th August 2017) - Vanderpool, Rebecca R.; Desai, Ankit A.; Knapp, Shannon M.; Simon, Marc A.; Abidov, Aiden; Yuan, Jason X.-J.; Garcia, Joe G.N.; Hansen, Lillian M.; Knoper, Steven R.; Naeije, Robert; Rischard, Franz P.
Within recent years, right ventricular (RV) function has been recognised as a major determinant of outcome in pulmonary arterial hypertension (PAH) [1, 2]. Clinical [3] and in vitro experimental [4, 5] data suggest that prostacyclins, the treatment of choice for most severely ill PAH patients [6], might have a positive inotropic effect on RV function, and reduce pulmonary vascular resistance (PVR). Nevertheless, inotropic effects are difficult to demonstrate in vivo, as ventricular contractility adjusts to afterload to preserve ventricular-arterial coupling [7]. In fact, the ratio of ventricular end-systolic elastance (Ees), a measure of in vivo contractility, to pulmonary arterial elastance (Ea) or the "coupling ratio" (Ees/Ea), was restored by epoprostenol in a model of load-induced acute RV failure; however, this was explained by a reduction in afterload [8]. Prostacyclin reduces right ventricular contractility, but improves ejection fraction and exercise capacity in PAH http://ow.ly/m5S830dpcZv